Long‐term effects of systemic gene therapy in a canine model of myotubular myopathy. Issue 5 (22nd May 2017) - Elverman, Matthew; Goddard, Melissa A.; Mack, David; Snyder, Jessica M.; Lawlor, Michael W.; Meng, Hui; Beggs, Alan H.; Buj‐Bello, Ana; Poulard, Karine; Marsh, Anthony P.; Grange, Robert W.; Kelly, Valerie E.; et al.
ABSTRACT: Introduction: X‐linked myotubular myopathy (XLMTM), a devastating pediatric disease caused by the absence of the protein myotubularin, results from mutations in the MTM1 gene. While there is no cure for XLMTM, we previously reported effects of MTM1 gene therapy using adeno‐associated virus (AAV) vector on muscle weakness and pathology in MTM1 ‐mutant dogs. Here, we followed 2 AAV‐infused dogs over 4 years. Methods: We evaluated gait, strength, respiration, neurological function, muscle pathology, AAV vector copy number (VCN), and transgene expression. Results: Four years following AAV‐mediated gene therapy, gait, respiratory performance, neurological function and pathology in AAV‐infused XLMTM dogs remained comparable to their healthy littermate controls despite a decline in VCN and muscle strength. Conclusions: AAV‐mediated gene transfer of MTM1 in young XLMTM dogs results in long‐term expression of myotubularin transgene with normal muscular performance and neurological function in the absence of muscle pathology. These findings support a clinical trial in patients. Muscle Nerve 56 : 943–953, 2017